Vaginal “tunnel flap” technique for urethral neomeatus reconstruction after distal urethrectomy in advanced vulvar cancer: a case report with anatomical insights - Ceccaroni, Marcello; Ferrari, Filippo Alberto; Roviglione, Giovanni; Bruni, Francesco; Mantovani, Giulia; Bogani, Giorgio; Cristofoli, Cesare; Masini, Gaia; Leone Roberti Maggiore, Umberto (Frontiers in Medicine, 2025)
Vulvar cancer with distal urethral involvement requires radical surgery that can severely impact urinary function and quality of life. Urethral neomeatus reconstruction therefore, represents a critical yet underexplored challenge in gynecologic oncology. We report a novel vaginal “tunnel flap” technique designed to recreate a functional urethral outlet after radical vulvectomy and distal urethrectomy. The flap leverages detailed knowledge of the urethrovaginal septum and its vascular supply to create a well-vascularized mucosal tunnel that reproduces native urethral morphology while minimizing suture line tension and the risk of postoperative stenosis. In the presented case report, despite early wound-healing complications, suprapubic urinary diversion enabled complete recovery. Long-term follow-up showed sustained oncologic control, excellent urinary function, preserved sexual activity, and satisfactory aesthetic results. This report highlights the role of precise surgical anatomy in optimizing reconstructive outcomes and proposes a reproducible technique that balances oncologic safety with functional and aesthetic preservation.